“Categoria especial da sociedade”: estudo do patrimônio cultural e da representatividade social da Força Expedicionária Brasileira – FEB - Calikevstz, Viviane Regina (2017)
The present thesis aims to show the representativeness of the social category of the Brazilian Expeditionary Force - FEB, as a special category of society. The time period in question dates from the decades of consolidation of the Regime do Estado Novo - from the 1930s to the present day, through pre and post World War II stages, showing how the category was built, its performance in the world conflict, its return home as heroes, its abandonment by the State and its materialization in the form of symbols throughout national territory. In the search for the confirmation of the hypothesis that it would be the category of the FEB and its members, living assets of society, which generated the question of the military heritage and its representativeness in the form of symbols. These being the FEB category itself, its monuments , museums, virtual memory spaces, private collections and memoirs of living veterans and individuals in general, cultural productions such as films, documentaries and books, created and developed for researchers, writers, filmmakers, admirers, family members and war veterans themselves. As an interdisciplinary research project, the approaches used included several humanistic chains, based on authors and the concepts of disciplines such as geography, history, sociology and arts, showing that the complexity of the theme and the hypotheses, which called for this large a range of scientific approaches. The research presents acceptable proof and conclusions, but is not fully closed, since the construction process itself, still ongoing, was the most evident element at work.